Model Penyelesaian Konflik Sosial Hutan Adat Pubabu Di Desa Linamnutu Kecamatan Amanuban Selatan Kabupaten Timor Tengah Selatan - Serfina Hoar Klau; Robertus Robertus; Johannis N. Kallau (International Forum of Researchers and Lecturers, 2023)
This study aimed to describe the model of social conflict the resolution costumary forest Pubabu. The focus of this research study is history of forest position Pubabu costumary, root of the problem of social conflict the traditional forest Pubabu and model of conflict resolution the costumary forest social Pubabu. The method of this study is qualitative oriented. Some techniques of data collecting in this study are interview, field observation, field note and document study. Technicques of data collectin in this study is interactive by Miles and Huberman with itssteps of process: data collecting, reduction, verification, data presentation. The results obtained from this study as follows: 1). Costumary forest and costumary society, 2). Cooperation of between the community and the government so that happened the social conflict of the costumary forest Pubabu in the management of costumary forest by society and government with base perspective and aimed of different which one of start conflict the costumary forest of logging in the year 2003, 2006, 2008, 3). Minister of the environment of regulation the number 83 year 2016 about is social forestry that 5 offer concept are: village forest, community forest, plant forest society, costumary of forest and community partnership. But of the 5 it concept offers, aspirations of costumary society is costumary forest; The forest owned by indigenous people previously it was a state forest or not state forest. Costumary forest are owned by community and the forest by community and the forest management costumary it managed by indigenous peoples. This concept becomes aspiration costumary society Pubabu, the beginning of the struggle until now.